An??lise do impacto da vacina antimeningoc??cica e dos gastos com hospitaliza????o da doen??a meningoc??cica em crian??as menores de 4 anos no munic??pio de S??o Paulo, SP, 2007 a 2015 - Machado, Eliana (2019)
World Public Health demands organized efforts by society to protect, promote and restore the health of populations and faces complex challenges. The health diagnosis helps in the planning of health actions, thus constituting an important tool for Health Services Management. The assessment of the health-disease situation of a population has as an important tool the Epidemiology in Health, which, through the use of their methods of study, it is possible to base the strategies of control and prevention of health problems, as well as the planning and management of health services. This evaluation can be done from health indicators that are summary measures that capture relevant information from different attributes and dimensions of health, used internationally. This study aims to analyze indicators of Meningococcal Disease (MD), which can evidence the impact of the implantation of the anti-meningococcal vaccine in the incidence rates, mortality and hospitalization and hospitalization costs in children under 4 years of age in the city of S??o Paulo from 2007 to For the collection and calculation of the indicators, secondary data of the information systems were used, available on the website of the Department of Information of SUS - DATASUS of the Ministry of Health, such as: Information System of Hospitalization SIH-SUS and Information System of Notification Diseases - SINAN. A total of 1418 confirmed cases of DM for the age group of 0 to 4 years and 353 confirmed cases for the control age range of 10 to 14 years were evaluated in the period from 2007 to 2015. For the age group 0 to 4 years (p = 0.04) in the incidence rate, a reduction of 68.04% (p = 0.02), a reduction in the mortality rate, a reduction of 49.69% (p = 0.03) in the hospitalization rate and a reduction of 53.81% (p = 0.06) in hospitalization costs for DM. A negative percentage change of 60.8% was also calculated for the proportions between Hospitalization Expenditures in the SUS for MD and Expenditures with Hospitalization in the SUS for all categories for the 0-4 age group. The impact of the vaccine was higher in all the variables studied, for the age group 0 to 4 years, contemplated by the vaccine, when compared to the 10 to 14 year age group (control) not contemplated by the National Immunization Program (PNI).